1978
DOI: 10.1159/000128008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slow Intravenous Administration of Endotoxin on Blood Cells and Coagulation in Dogs

Abstract: Endotoxin shock was induced in dogs by slow administration of a lethal dose of Escherichia coli endotoxin. During the 3-hour infusion period a state of disseminated intravascular coagulation (DIC) was noted. The drop in platelets and leukocytes was the most rapid and pronounced effect of the infusion, while consumption of coagulation factors occurred more slowly. Activation of the extrinsic and intrinsic pathways of coagulation appeared to be closely parallel. Concomitantly increasing amounts of fibrin(ogen) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 26 publications
(34 reference statements)
2
11
0
Order By: Relevance
“…prekallikrein, kininogen, kininases) have been investigated. Previously we reported that plasma levels of prekallikrein and Hageman factor fall markedly in the late stages of endotoxin-induced shock in dogs (1,3) further results in cluding changes in levels of high molecular weight kininogen and kallikrein inhibitors are reported in this article.…”
Section: Introductionsupporting
confidence: 72%
“…prekallikrein, kininogen, kininases) have been investigated. Previously we reported that plasma levels of prekallikrein and Hageman factor fall markedly in the late stages of endotoxin-induced shock in dogs (1,3) further results in cluding changes in levels of high molecular weight kininogen and kallikrein inhibitors are reported in this article.…”
Section: Introductionsupporting
confidence: 72%
“…The blood hemoglobin and hematocrit values in the control group did not differ significantly (table II) from those of the endotoxemia group, although there was a moderate hcmoconccntration in the animals of the latter group as described by other authors, too [1]. Endo toxin infusion caused a substantial and rapid decrease of circulating plate lets (starting value: x = 251.700 ± 22,923 cells/pl; 2-hour value: x = 98.233 ± 18,396 cells/pl).…”
Section: Endotoxemia Modelsupporting
confidence: 61%
“…Two horses (20,23) experienced hemorrhagic diathesis during the coagulopathy. Four horses were treated with heparin ( 18,19,20,2 l), one horse received plasma (22), and one horse (23) received both heparin and plasma treatment.…”
Section: Resultsmentioning
confidence: 99%